Extraocular Technique of Intrascleral Intraocular Lens Fixation Using a Pair of the Shaft-Bended 27-Gauge Needles. Issue 1 (January 2017) - Maruko, Ichiro; Koizumi, Hideki; Kogure-Katakura, Akiko; Iida, Tomohiro
Abstract : Supplemental Digital Content is Available in the Text.